A certificação como fator indutor da melhoria da qualidade: o caso do selo ambiental do Instituto Rio Grandense do Arroz (IRGA) - Lhamby, Andressa Rocha (2013)
This work shows a research relating to certification as a factor of inducer quality, your implications and benefits about agribusiness, with main object of study the IRGA case of environmental seal. Considering the environmental degradation, the managers and investors have been thinking more and more on innovative strategies that seek the environmental quality and the minimization of investiments, being through the adoption of eco-friendly raw materials or through the adoption of programs for environmental quality. These programs seeking to optimize certain productives processes, reducing unnecessary losses, securing quality to consumers and respecting the ambiental environmental. This research has as objective to interpret the criteria of the certification process adopted by the IRGA environmental seal, to characterize the profile of the rural organization certified, to identify which are the practices adopted to attend the requirements and to analyze like the environmental seal contributes to the fulfillment of the current ambiental environmental legislation, increase of the productivity and quality improvement. This research is classified as exploratory, bibliographic and study case. The mains strategies of improvement adopted by producers in the certification process are direct seeding, crop rotations, selective collection, training of good practices to reviewers and 5S.It is concluded that the IRGA environmental seal promotes the increase of the quality and productivity, besides facilitate the sustainable handling of the rice sector.